CAUSES AND EFFECTS OF THE PROTAGONIST’S WORRY IN DANIELLE STEEL’S NOVEL FAMILY TIES - Muhammad Ikhsan; Susi Ekalestari (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
This research analyses the causes and effects of the protagonist’s worry in Danielle Steel’s novel Family Ties, a story of woman, Annie Ferguson, who must become a mother in her bachelorette. She always worries about the future of her sister’s children. This research applied the theory of worry proposed by Graham (2006), who said that worry is “prominent feature of most anxiety-based disorders including generalized anxiety disorder, specific phobias obsessive-compulsive disorder, panic disorder, and post-traumatic stress disorder“. The research is completed by using descriptive qualitative method in which the finding is presented in the form of description. The data of this study is obtained from the novel Family Ties by Danielle Steel. The analysis finds that the dominant causes of the protagonist’s worry come from her nephews’ life which affects her life negatively. The effects of her worry will be a lesson for human life because every human being certainly has worry feeling in their life in certain situations.